2018
DOI: 10.1113/jp276557
|View full text |Cite
|
Sign up to set email alerts
|

Lower body negative pressure to safely reduce intracranial pressure

Abstract: Key points During long‐term missions, some astronauts experience structural and functional changes of the eyes and brain which resemble signs/symptoms experienced by patients with intracranial hypertension. Weightlessness prevents the normal cerebral volume and pressure ‘unloading’ associated with upright postures on Earth, which may be part of the cerebral and ocular pathophysiology. By placing the lower body in a negative pressure device (LBNP) that pulls fluid away from cranial compartments, we simulated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS. [73][74][75][76][77][78][79][80][81][82] These countermeasures include metabolic and pharmacologic treatments 69,[83][84][85][86][87] in the one carbon pathways; 63,69 lower body negative pressure; [74][75][76] and swim goggles to affect the translaminar pressure gradient. While current data does not seem to support prolonged, significant elevations of ICP to the levels seen in IIH, throughout LDSF, Lawley et al proposed that even mild elevations of ICP for a prolonged duration may contribute to the structural changes seen in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS. [73][74][75][76][77][78][79][80][81][82] These countermeasures include metabolic and pharmacologic treatments 69,[83][84][85][86][87] in the one carbon pathways; 63,69 lower body negative pressure; [74][75][76] and swim goggles to affect the translaminar pressure gradient. While current data does not seem to support prolonged, significant elevations of ICP to the levels seen in IIH, throughout LDSF, Lawley et al proposed that even mild elevations of ICP for a prolonged duration may contribute to the structural changes seen in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…2004; Petersen et al . 2019) and dampened the increase of SV and MAP at the brain and heart levels. Also, the counteractive effect of LBNP against −Gz on HR and SV vanished after 5 s with the increase of −Gz (−0.50 to −0.87 G).…”
Section: Resultsmentioning
confidence: 98%
“…Under normal compensatory adaptations, the ICP stays within a narrow pressure range for each assumed body posture [20, 21]. This is the simplest way of looking at ICP, as just a number that should remain within certain boundary values.…”
Section: Discussionmentioning
confidence: 99%